THE EFFECT OF PRENATAL YOGA ON REDUCING ANXIETY IN TRIMESTER III PREGNANT WOMEN: A NARRATIVE REVIEW - Ida Maryati; Furri Fuzie Lestari; Milda Khaerunnisa; Nenden Novitasari; Syefira Salsabila; Syifa Melya Fauziyah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Anxiety is a common reaction and the inability to deal with problems, can happen to anyone, including third trimester pregnant women who are facing labor. The impact caused by the victim, namely postpartum depression, premature delivery, and behavioral disorders in children (baby blues). One of the non-pharmacological techniques to reduce it is prenatal yoga. Prenatal yoga has a positive impression for pregnant women which reduces stress, discomfort, pain during pregnancy, and reduces labor pain. This study aims to determine the effect of prenatal yoga on reducing anxiety in third trimester pregnant women.The type of literature review used a narrative review, and the approach used in the search for articles using PICO. Search for articles was carried out using the Google Scholar, PubMed, Sciencedirect, EBSCO, and National Library databases. The search results for articles from all of these databases were 9,338, but after being selected with inclusion and exclusion criteria, 8 journals were obtained for review From the 8 journals selected, the average respondent showed a decrease in the anxiety scale. From the results of a review of 8 selected journals, it was explained that there was an effect of prenatal yoga on reducing anxiety in pregnant women, with an average p-value of 0.000 (p <0.05). The duration of effective prenatal yoga was 2 times a week and the types of effective exercises were deep breathing techniques, stretching muscles, and meditation.